Cerium(IV) ammonium nitrate promoted synthesis of O-phthalimide oximes from vinyl azides and N-hydroxyphthalimide. Issue 47 (19th November 2020) - Paveliev, Stanislav A.; Alimkhanova, Liliya S.; Sergeeva, Anna V.; Terent'ev, Alexander O.
Graphical abstract: Highlights: Cerium(IV) ammonium nitrate as a reagent for radical oxidative transformations. Preparative generation of imide- N -oxyl radicals from N -hydroxyphthalimide. Addition of O-centered imide- N -oxyl radicals to double carbon–carbon bonds. Reactions involving vinyl azides with the formation of iminyl radicals. Formation of NO bond through the recombination of N- and O-centered radicals. Abstract: O -Phthalimide oximes with an NON fragment were synthesized in high yields via the reaction of vinyl azides with phthalimide- N -oxyl radicals derived from N -hydroxyphthalimide under the action of cerium(IV) ammonium nitrate. The disclosed process is based on the radical transformation of vinyl azides with the elimination of nitrogen and the formation of iminyl N -radicals. The developed approach exploited the dual reactivity of imide- N -oxyl radicals. They act as O-components for oxidative CO coupling with vinyl azides and participate in subsequent formation of the NO bond via their recombination with intermediate iminyl radicals.